Combined voltage stability index for charging station effect on distribution network - Jamian, J.J.; Musa, H.; Mustafa, M.W.; Mokhlis, Hazlie; Adamu, S.S. (Praise Worthy Prize, 2011)
This paper presents the effect of Distributed Generation (DG) as well as Charging Station (CS) to the voltage stability index (VSI) on distribution network Various locations for CS within the network are used in order to evaluate the effect of increment of the CS. The DG that is used is operated in PV mode. There are three types of VSI formulae applied to indicated the condition of the network as either collapsed or not which are P-VSI, Q-VSI (known as FVSI) and C-VSI. The study clearly shows that the increment of CS and location of DG has greater impact on Q-VSI and P-VSI towards attaining voltage collapse point. Further study conducted has reviled that voltage collapse indication in radial distribution network is better monitored by use of the Combined VSI ( C-VSI). The analysis was tested on a 33 bus distribution system.